Tingkat pemahaman finansial literasi terhadap gaya hidup mahasiswa - Adinda, Adinda; Ifrah, Marsyanda; Kurnianingsih, Heny Triastuti (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
To ascertain the Islamic University of North Sumatera pupils' comprehension of financial literacy. The growing prevalence of impulsive purchases and consumer behavior that goes beyond acceptable bounds begs the important issue,